Conditions for late gadolinium enhancement MRI in myocardial infarction model rats that better reflect microscopic tissue staining - Junpei Ueda; Hayato Kurata; Miwa Ota; Isamu Yabata; Koji Itagaki; Reika Sawaya; Chiharu Murata; Natsuo Banura; Hiroyuki Nishida; Shigeyoshi Saito (Scientific Reports, 2024)
Abstract Late gadolinium enhancement (LGE) is a widely used magnetic resonance imaging method for assessing cardiac disease. However, the relationship between different LGE signal thresholds and microscopic tissue staining images is unclear. In this study, we performed cardiovascular MRI on myocardial infarction (MI) model rats and evaluated the relationship between LGE with different signal thresholding methods and tissue staining images. We prepared 16 rats that underwent MRI 14–18 days following a surgery to create an MI model. We captured cine and LGE images of the cardiac short-axis and longitudinal two- and four-chamber views. The mean ± 2SD, ± 3SD, and ± 5SD of the pixel values in the non-infarcted area were defined as the LGE area. We compared areas of Sirius red staining, determined by the color tone, with their respective LGE areas at end-diastole and end-systole. We observed that the LGE area calculated as the mean ± 2SD of the non-infarcted area at end-diastole demonstrated a significant positive correlation with the area of Sirius red staining (Pearson’s correlation coefficient in both: 0.81 [p < 0.01]). Therefore, the LGE area calculated as the mean ± 2SD of the non-infarcted area at end-diastole best reflected the MI area in tissue staining.